Secrecy Jurisdictions - Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper surveys tax haven legislation and links the literature on tax havens to the literature on asymmetric information. I argue that the core aim of tax haven legislation is to create private information (secrecy) for the users of tax havens. This leads to moral hazard and transaction costs in non-havens. The business model of tax havens is illustrated by using Mauritius and Jersey as case studies. I also provide several real world examples of how secrecy jurisdictions lead to inefficient market outcomes and breach of regulations in non-haven countries. Both developed and developing countries are harmed, but the consequences seem most detrimental to developing countries.
Keywords: H25; F23; O10; 330; tax havens; secrecy; private information; moral hazard